Takeovers of Privately Held Targets, Methods of Payment, and Bidder Returns - Chang, Saeyoung (Journal of Finance, 1998)
We examine bidder returns at the announcement of a takeover proposal when the target firm is privately held. In stock offers, bidders experience a positive abnormal return, which contrasts with the negative abnormal return typically found for bidders acquiring a publicly traded target. On the other hand, bidders experience no abnormal return in cash offers. Our analysis suggests that the positive wealth effect is related to monitoring activities by target shareholders and, to an extent, reduced information asymmetries.